SISTEM INFORMASI PENGGAJIAN KARYAWAN KONTRAK DI PT. KIB - FIHARTANTI, FIHARTANTI; Utomo, Agus Prasetyo (Information Technology and Telematics, 2018)
Abstract Employee payroll is a thing done by a company to fulfill its obligation, one of which is the concract employee’s payroll at PT. KIB. As for the background of this writing because at PT. KIB has been competerized but it is still less efective and also for production employees cannot know the details of the payroll. Personnel feel overwhelmed for the payroll process for production employee so that by utilizing the php programming language, html, and the mysql database which is then designed a website-based system can help personnel to process payroll efectively and efficiently and benefit production employees because with this system employees can find out payroll detail.